THE IMPLEMENTATION OF LOW-COST EDUCATIONAL VIDEOS TO IMPROVE STUDENTS’ PERFORMANCE IN TOEIC PREPARATION TEST - Atiqah Nurul Asri; Faiz Ushbah Mubarok; Aly Imron (University of Kuningan, 2022)
This paper was aimed to improve Information Technology students’ performance in the TOEIC International test by using low-cost videos. The test was held by the State Polytechnic of Malang together with the International Test Center (ITC) to compete in this 4.0 industrial era. Due to the pandemic condition, the research was conducted online using the Learning Management System (LMS) and the Zoom application. The subjects in the study were a class consisting of 28 final year students of the Informatics Management Study Program. In this research, we applied Class Action Research (CAR) in 2 cycles, the first cycle was six meetings and the second cycle was two meetings. This study was said to be successful if at least 70% of the students got a score above 450 points. Next, TOEIC pre-test and post-test scores were analyzed using the T-test. In addition, this study also analyzed students' perceptions of the learning model. From the results of the T-test analysis from the pre-test, post-test 1, and post-test 2, it can be concluded that this learning model could increase TOEIC scores. Based on the results of the questionnaire and observations, it showed that students responded mostly positive feedback and improved students’ performance in TOEIC scores.